Comportamento criativo em equipes de telejornalismo: a atuação da liderança em emissoras de TV - Roldan, Vivianne Pereira Salas (2012)
This work was developed in order to analyze the management of creativity in cultural organizations, whose context the leaders brings a series of dilemmas about the best resolutions to be taken. The chosen field was the television industry and the units of analysis were the television news teams from TV Assembleia, TV Jangadeiro and TV O POVO. In the television field, managers are challenged to learn how to create practices and policies that encourage journalists to produce high quality programs, and make use of intervention strategies that lead to creative processes desired efficacy. The aim of this study was to analyze the role of leadership for the promotion of creative behavior in work teams in television news companies TVs Ceará. As specific objectives, the research sought to: 1) To analyze the performance of the creative teams of TV Journalism and its relationship with the leadership style; 2) Check the specifics of the context and role of leadership; 3) Investigate the differences in performance between the leaders of the organizations studied. The work followed a qualitative and quantitative approach, characterized as descriptive as to the purposes. As instruments of data collection, applied the questionnaire model for Creative Leadership Rickards and Moger (2000) with leaders and teams of television news. A second questionnaire and a semi-structured interviews were applied to leaders, to deepen the study. It was found that the leaders of the TV stations make use of these combined strategies of the style of transactional and transformational leadership to lead their teams. Nevertheless, the quantitative results of the Spearman correlation suggests that in the context of TV Jangadeiro and TV Assembleia there is a greater relationship between transformational leadership, the factors of creative leadership, and team performance with respect creativity, productivity and knowledge management. For the TV O POVO, the correlation analysis suggests that both leadership styles are positively related with the factors of creative leadership. With respect to team performance, suggests that transactional leadership applied by managers contributes to the best knowledge management team.